Impact of match results on the physical performance of players in Japanese elite Rugby Union match play - Yamamoto, H.; Takemura, M.; Tachibana, M.; Tsujita, J.; Hojo, T. (International Journal of Sport & Health Science, 2020)
Purpose: The purpose of this study was to analyze the impact of match results (win-loss, score differential) on the physical performance of rugby union teams to improve training and conditioning and provide ideas for use on the playing field.